1999
DOI: 10.4269/ajtmh.1999.61.259
|View full text |Cite
|
Sign up to set email alerts
|

A new monospecific ovine Fab fragment antivenom for treatment of envenoming by the Sri Lankan Russell's viper (Daboia Russelii Russelii): a preliminary dose-finding and pharmacokinetic study.

Abstract: Abstract. Russell's viper is the most important cause of life-threatening snake bite and acute renal failure in Sri Lanka. Only equine polyspecific antivenoms imported from India are available. They have not proved effective clinically or in clearing venom antigenemia and they frequently cause reactions. In an attempt to reduce mortality and morbidity, a new monospecific ovine Fab fragment antivenom (PolongaTab ; Therapeutic Antibodies, Inc., London, United Kingdom) was raised against Sri Lankan Russell's vipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 25 publications
2
49
1
1
Order By: Relevance
“…For this to be true, there would be simultaneous detection of recurrent venom and clinical and/or laboratory evidence of envenoming. However, the vast majority of reports are of recurrent venom detection (antigenaemia) without recurrent envenoming (Ariaratnam et al, 1999;Ho et al, 1986;Phillips et al, 1988;Theakston, 1997). This is demonstrated in the study by Otero et al where they found recurrence of venom in serum samples in eight of 52 patients, 6e72 h post-antivenom, but no evidence of recurrent coagulopathy.…”
Section: Introductionmentioning
confidence: 81%
“…For this to be true, there would be simultaneous detection of recurrent venom and clinical and/or laboratory evidence of envenoming. However, the vast majority of reports are of recurrent venom detection (antigenaemia) without recurrent envenoming (Ariaratnam et al, 1999;Ho et al, 1986;Phillips et al, 1988;Theakston, 1997). This is demonstrated in the study by Otero et al where they found recurrence of venom in serum samples in eight of 52 patients, 6e72 h post-antivenom, but no evidence of recurrent coagulopathy.…”
Section: Introductionmentioning
confidence: 81%
“…On the other hand, low molecular mass Fab fragments have a relatively short half-life, thus resulting in the phenomenon of recurrence of envenoming, i.e. the reappearance of signs and symptoms of envenoming several hours after antivenom therapy (Ariaratnam et al, 1999;Boyer et al, 2001;Meyer et al, 1997). Careful clinical following up of patients is necessary to determine the need of an additional dose of antivenom.…”
Section: Clinical Performance Of Antivenoms: Efficacymentioning
confidence: 99%
“…For patients known to be sensitive to equine proteins, avoidance of antivenoms prepared in this manner is mandatory and should reduce the incidence of anaphylactic shocks. Some production laboratories are now successfully using other animals like sheep as sources of sera (7,28,39). Recent studies indicate the use of camels for antivenom production, due to lower in vitro complement activation than found in horses and sheep (40,41).…”
Section: Reaction)mentioning
confidence: 99%